Impact of Letrozole on Mature Follicle Rate in Treatment of Subfertility Due to Polycystic Ovarian Syndrome: Letrozole and Follicle Rate in Polycystic Ovarian Syndrome - Javeria, Mehvish; Noor, Lubna; Taj, Urfa; Hanif, Qurat Ul Ain; Hussain, Samar; Hanif, Asif (Pakistan Journal of Health Sciences, 2024)
Letrozole was an aromatase inhibitor that has gained prominence as an alternative to the clomiphene citrate for ovulation induction in females with Polycystic Ovarian Syndrome (PCOS). Objective: To assess the frequency of mature follicle rate as a result of letrozole treatment in subfertility due to PCOS. Methods: This interventional study was performed at Obstetrics and Gynecology Department, Combined Military Hospital, Multan, over a period of 6 months, from March 1, 2023 to September 1, 2023. The study included 322 cases aged between 20–40 years, who reported infertility for longer than a year, had Body Mass Index (BMI) <28, and had subfertility due to PCOS. All study participants were subjected to letrozole treatment. Development of mature follicles was observed utilizing transvaginal ultrasound starting from the 10th day of treatment. Results: The mean age of patients was 32.82 ± 4.30 years. The mean weight was 61.74 ± 7.35 kg, whereas the mean height was 1.61 ± 0.069 m. The mean BMI was 23.68 ± 2.96 kg/m². Among the participants, 161 (50.0%) patients had primary infertility, and 161 (50.0%) had secondary infertility. After receiving letrozole treatment, 237 (73.6%) patients had mature follicles on ultrasonography. Conclusions: Letrozole seems to improve the rate of follicle maturation in women with subfertility due to PCOS, thereby increasing the likelihood of pregnancy. Based on these findings, letrozole can be regarded as a suitable alternative to first-line therapies such as clomiphene citrate, providing favorable outcomes and minimal side effects, specifically in patients with clomiphene citrate resistance.